Action mechanism and cardiovascular effect of anthocyanins: a systematic review of animal and human studies - Jordano Ferreira Reis; Valter Vinicius Silva Monteiro; Rafaelli de Souza Gomes; Matheus Moraes do Carmo; Glauber Vilhena da Costa; Paula Cardoso Ribera; Marta Chagas Monteiro (Journal of Translational Medicine, 2016)
Abstract Cardiovascular diseases (CVD) are an important cause of death worldwide. Anthocyanins are a subgroup of flavonoids found in berries, flowers, fruits and leaves. In epidemiological and clinical studies, these polyphenols have been associated with improved cardiovascular risk profiles as well as decreased comorbidities. Human intervention studies using berries, vegetables, parts of plants and cereals (either fresh or as juice) or purified anthocyanin-rich extracts have demonstrated significant improvements in low density lipoproteins oxidation, lipid peroxidation, total plasma antioxidant capacity, and dyslipidemia as well as reduced levels of CVD molecular biomarkers. This review discusses the use of anthocyanins in animal models and their applications in human medicine, as dietary supplements or as new potent drugs against cardiovascular disease.